Systematic Training to Improve the Transformation of Migrant Workers into Industrial Workers within the Construction Sector in China - Yanyan Ke; Jing Bian (Buildings, 2023)
The transformation and modernization of the construction industry in China has introduced higher knowledge, skill, literacy, and innovation ability requirements for construction workers. Subsequently, more than 53 million migrant workers, comprising the main workforce of China’s construction sector, require transitioning into the roles of high-quality and highly skilled construction industry workers. As an important means to improve human capital, systematic training is the key method for the development of migrant workers into industrial workers within China’s construction industry. This paper constructs and verifies the theoretical model underlying the operating mechanism of the training system for migrant workers within the construction industry. As such, a structural equation model was established for the mechanism of transforming construction migrant workers into industrial workers. The results show that as the driving forces, the government and construction industry play important roles in promoting the operation of the training system for migrants in the construction industry as they provide internal vocational and social training. Construction enterprises have a direct role in promoting professional literacy training as one of the direct beneficiaries of construction workers’ training. Therefore, this paper provides a critical reference for policy promoting the transformation of migrant workers into industrial workers through appropriate training within China’s construction industry.